Penerapan LKPD Berbasis PBL untuk Meningkatkan Pemahaman Siswa Kelas IV di SD Negeri 105288 Sei Rotan : Penelitian - Asiah Ramadhani; Dini Agesti Siregar; Mufidatul Husna; Putri Nabila; Roma Ito Aruan; Siti Misharyani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This studies turned into encouraged with the aid of the low know-how and involvement of fourth grade students at SD Negeri 105288 Sei Rotan in wearing out easy experiments concerning the concepts of temperature and warmth in regular existence. to conquer this trouble, a pupil Worksheet (LKPD) based totally on problem based totally mastering (PBL) is implemented that's expected to increase college students' knowledge of the cloth. This studies pursuits to use the effectiveness of PBL-based totally LKPD in increasing college students' information of temperature and warmth studying thru candle and glass experiments. The research technique used is the experimental approach in lecture room motion research (PTK). on this studies, researchers collected records acquired at once in the subject through amassing records through observation, tests and documentation. The studies topics were fourth grade students at SD Negeri 105288 Sei Rotan with a complete of 35 students. The outcomes of this studies display that the software of experimental techniques mixed with PBL-based totally LKPD has a widespread nice effect on college students' information of temperature and warmth transfer. it is able to be concluded that this research makes an crucial contribution to the development of science gaining knowledge of strategies in elementary faculties, specifically in efforts to growth students' information of cloth this is frequently considered hard.